2021
DOI: 10.1177/20587384211036819
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin ameliorates hepatic steatosis by inhibiting NLRP3 inflammasome in db/db mice

Abstract: Introduction: Type 2 diabetes mellitus (T2DM) is commonly accompanied by obesity and non-alcoholic fatty liver disease (NAFLD), yet the mechanism underlying diabetes-related NAFLD is not fully understood. It has been reported that melatonin can regulate glucose and lipid metabolism. This study aims to investigate the actions and mechanisms of melatonin toward the development of diabetes-related NAFLD. Methods: Melatonin (bid, 30 mg/kg/day, i.p.) was administrated to db/db mice for 8 weeks, while saline was adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Hyperglycemia leads to various complications, including cirrhosis and eventually hepatocellular carcinoma [29]. Db/ db mice have consistently elevated levels of liver weight and liver glycogen [30,31], accompanied by liver steatosis, aggravated fbrosis [32]. Our results showed that T-fber could improve the liver weight compared with the model group.…”
Section: Discussionmentioning
confidence: 60%
“…Hyperglycemia leads to various complications, including cirrhosis and eventually hepatocellular carcinoma [29]. Db/ db mice have consistently elevated levels of liver weight and liver glycogen [30,31], accompanied by liver steatosis, aggravated fbrosis [32]. Our results showed that T-fber could improve the liver weight compared with the model group.…”
Section: Discussionmentioning
confidence: 60%
“…In addition, the study made use of a genetic model of obesity and diabetes, which may differ from the human phenotype [ 37 ]. However, the homozygous diabetic leptin-resistant BKS.Cg-Dock7m+/+ Leprdb/J ( db/db ) mice model used here has been a useful tool in studies of liver dysfunction, as the animals have previously been shown to exhibit hepatic steatosis and lobular inflammation, along with significantly elevated alanine transaminase, aspartate aminotransferase, total cholesterol and triglyceride levels as compared with non-diabetic mice [ 38 , 39 ]. To address several of the highlighted limitations, the use of a high-fat, high-cholesterol diet model of hepatic steatosis in rodents may be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that NLRP3 is expressed in a variety of cells and its mediated signaling pathway plays an important role in the progression of diabetes [ 35 , 36 ]. Several studies have shown that activation of NLRP3 can stimulate inflammatory formation and pyroptosis of cells [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%